Etude Archeothanatologique De La Sepulture Protohistorique Du Monument Funeraire Mbii (Boulmane, Moyen Atlas, Maroc) - khaddouje, Benlamine Lalla; Mohammed, Benabdelhadi; Aicha, Oujaa; Nassareddine, Azzouzi; Soumaya, Benabdelhadi; Michel, Fontugne (European Scientific Journal, ESJ, 2017)
The Moudmane Boulama site is a funeral structure located at 10 km South West of the city of Boulmane (Middle Atlas). It is a necropolis made of approximately twenty tumuli implanted on a hill. The MBII funeral monument is a tumulus built on the top of this hill, which culminates at 1970 m. It is an oval formation made of stack of stones and blocks. The funeral space is delimited in its West part by a low wall made of a sharpened stone alignment. The digs undertaken in June 2013 brought to light the burial place of a H3 adult and some remains of another adult as well as an immature subject. The skeleton of the most complete H3 individual is a male adult, buried in a lying dorsal position, oriented towards East West, head towards West and feet East. He is in a hyper contracted position and lays on an oval plane pit with a diameter of less than a meter. The calvarium and the mandible were subjected to a rotation and lay on the right side. The superior members are folded on themselves and laid on the thorax. The inferior members are also flexed. The skeleton is characterised by the maintaining of the connection of a number of labile elements which allows the characterisation of the burial place as being primarily in clogged space. This funeral monument has probably been used at first for the reception of the two individuals (H1 and H2) and then for the burial of the H3 individual in a sepulchral pit. The reuse of the monument could be explained by the three individuals belonging to the same family and that the last buried subject H3 has a more important familial and possibly social role. This tumulus has also released funeral furniture made of a few bones of domestic fauna. They were the object of a radiometric dating, which allowed the attribution of 2290 ± 35 years old to this tumulus14C B.P (GifA15085/ Sac A 41509).